(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article analyzes a series of poems dedicated to Khudoyorkhan (1831-1882), the last ruler of Kokand. Several poetic series were created by the creators of the period in connection with the Khan’s accession to the throne, his abdication, as well as the magnificent palace built by the Khan, and through the works of the authors, their individual approach to the issue of the Khan’s fate, worldview, and expressive image elements were examined. Issues such as the main idea and content of the poems, composition, interrelationship of the poems, unity of style, harmony of rhythm and melody, the poet’s artistic skill, and the expression of inner feelings were scientifically covered.